Cardiac sarcoidosis - Zacek, Pavel; Omran, Nedal; Chek, James L; Krbal, Lukas; Vojacek, Jan; Harrer, Jan (Journal of cardiac surgery, 2013)
Cardiac sarcoidosis is a rare entity and may be difficult to diagnose prior to cardiac surgery. We review the imaging and diagnostic studies necessary to make the diagnosis and discuss therapeutic algorithms to manage this disease.
Keywords: senioři; trikuspidální insuficience; lidé; Humans; diagnostické zobrazování; Diagnostic Imaging; fibrilace síní; Atrial Fibrillation; Heart Block; Female; sarkoidóza; Myocardium; Tricuspid Valve Insufficiency; Aged; Cardiomyopathies; Ventricular Dysfunction, Left; ženské pohlaví; anuloplastika srdeční chlopně; Mitral Valve Insufficiency; kardiomyopatie; Cardiac Valve Annuloplasty; mitrální insuficience; dysfunkce levé srdeční komory; Fatal Outcome; srdeční blokáda; Sarcoidosis; fatální výsledek; myokard